2020
DOI: 10.1038/s41598-020-60482-9
|View full text |Cite
|
Sign up to set email alerts
|

SLPI - a Biomarker of Acute Kidney Injury after Open and Endovascular Thoracoabdominal Aortic Aneurysm (TAAA) Repair

Abstract: Acute kidney injury (AKi) is a relevant complication following thoracoabdominal aortic aneurysm repair (tAAA). Biomarkers, such as secretory leucocyte peptidase inhibitor (SLpi), may enable a more accurate diagnosis. in this study, we tested if SLpi measured in serum is an appropriate biomarker of AKi after TAAA repair. In a prospective observational single-center study including 33 patients (51.5% women, mean age 63.0 ± 16.2 years) undergoing open and endovascular aortic aneurysm repair in 2017, SLPI was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…The trial is registered under the ClinicalTrials.gov number NCT03093857. The cohort of patients has been previously described in a recently published study [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The trial is registered under the ClinicalTrials.gov number NCT03093857. The cohort of patients has been previously described in a recently published study [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…MIF-2 improved the recovery of injured epithelial cells by enhancing cell regeneration through secretory leukocyte proteinase inhibitor (SLPI) and activating transcription factor (ATF) 4-dependent mechanisms (83). SLPI has proliferative, antioxidant and cytoprotective properties, and is being evaluated as a biomarker for AKI after surgery (84)(85)(86).…”
Section: Mif-cd74 Pathway In Recovery From Kidney Injurymentioning
confidence: 99%
“…SLPI, secretory leukocyte peptidase inhibitor,among the top 5 DEGs up-regulated by CASP3 siRNA (Table 3), was renoprotective in experimental ischemia AKI (Ochi et al, 2017). SLPI inhibits nuclear factor kappa beta (NF-κB) signaling pathway (Tang et al, 2020) and the maturation of IL-1β (Zakrzewicz et al, 2019), and showed as a biomarker candidate in AKI (Averdunk et al, 2019;Averdunk et al, 2020). In human, SERPINA3, a member of the serpin superfamily of protease inhibitors, could limit inflammation by targeting cathepsin family (proinflammatory enzymes) (Horvath et al, 2005;Lannan et al, 2012).…”
Section: Downloaded Frommentioning
confidence: 99%